Design and implementation of a high-precision turbidity measuring instrument of a mine. Issue 1 (December 2019) - Wang, Xueming; Chen, Baoyuan; Zhang, Libin
Abstract: In this paper, the principle of turbidity detection based on light scattering principle is expounded, and a design method of high-precision turbidity measuring instrument in coal mine is proposed. The software and hardware design of such turbidity measuring instrument are introduced. The measuring instrument adopts integrated circuit design such as imported photodiode and high-precision operational amplifier. The MATLAB simulation software tool is used to formulate the curve of the turbidity measurement data, and the turbidity measurement value is compensated and corrected to improve the turbidity measurement accuracy. Furthermore, the measuring instrument adopts low-power design, the OLED display technology in particular, to replace the traditional digital tube or LCD liquid crystal; the anti-interference design is applied in the digital interface communication design, and the electromagnetic compatibility test is very suitable for the electromagnetic environment in the coal mine